2011
DOI: 10.3109/13880209.2011.604334
|View full text |Cite
|
Sign up to set email alerts
|

Identification, quantification of bioactive constituents, evaluation of antioxidant andin vivoacute toxicity property from the methanol extract ofVernonia cinerealeaf extract

Abstract: V. cinerea extract has significant (p < 0.05) antiradical activity. Hence, V. cinerea may have potential medicinal value and can be used in the formulation of pharmacological products for degenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Similarly, Vernonia condensata leaves aqueous extract did not present mutagenic potential using Salmonella/microsome assay (Monteiro et al, 2001). Moreover, the aqueous extract of Vernonia amygdalina and the methanol extract of Vernonia cineria present no toxicity in murine model (Amole et al, 2006;Rajamurugan et al, 2011). However, previous study with Swiss albinus mice demonstrated that V. polyanthes leaves hydroalcoholic extract presented a moderated genotoxic effect only in concentrations higher than 1500 mg/kg (Jorgetto et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Vernonia condensata leaves aqueous extract did not present mutagenic potential using Salmonella/microsome assay (Monteiro et al, 2001). Moreover, the aqueous extract of Vernonia amygdalina and the methanol extract of Vernonia cineria present no toxicity in murine model (Amole et al, 2006;Rajamurugan et al, 2011). However, previous study with Swiss albinus mice demonstrated that V. polyanthes leaves hydroalcoholic extract presented a moderated genotoxic effect only in concentrations higher than 1500 mg/kg (Jorgetto et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Administration of Vernonia cinerea extracts in mice significantly increases the level of anti-oxidant markers such as catalase, superoxide dismutase, glutathione, glutathione peroxidase and glutathione-S transferase in blood and liver, whereas lipid peroxidation activity was significantly decreased (Pratheeshkumar and Kuttan 2010, Kuttan 2009, Rajamurugan et al 2011). Recent reports suggested that Vernonia cinerea has analgesic, anti-inflammatory, antioxidant, radical scavenging and inhibition of pro inflammatory cytokines like TNF-alpha (Pratheeshkumar and Kuttan 2010, Rajamurugan et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…This plant has been reported in the presence of secondary metabolites like flavonoids, tannins, sesquiterpene lactones, sterols and triterpenoids (Misra et al 1993). Flavonoids such as luteolin, apigenin, chrysoeriol, quercetin, rutin, stigmasterol-3-Obeta-D-glucoside, (+)-lirioresinol B, stigmasterol and coumaric acids like caffeic acid, ferulic acid and terpenoids like lupeol acetate were reported from this plant (Rajamurugan et al 2011, Zhu et al 2008. Fresh decoction of Vernonia cinerea has been commonly used to relieve muscular pain, knee pain and severe headache in some areas of Palani, Vadalur and Ramanathapuram regions in Tamil Nadu, India.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, a greater significance has been attributed to ethnomedicine, involving the use of medicinal plants for effective treatment of cancer (Cordell, grows as a weed, and considered as a sacred plant, known as 'Dasapushpam' is medicinally significant to the people of Kerala in India (Varghese et al, 2010;Arun Raj et al, 2013b). In a traditional system of medicine, VC has been used for the treatment of various diseases including cancer (Bajpai et al, 1995;Kala, 2005;Varghese et al, 2010;Rajamurugan et al, 2011;Pratheeshkumar and Kuttan, 2012;Arun Raj et al, 2013a;Toyang and Verpoorte, 2013;Nataru et al, 2014). The chemical investigations suggest that VC contains triterpenes, sterols, phenolic resin, and sesquiterpene lactones (Pratheeshkumar and Kuttan, 2010;Varghese et al, 2010).…”
Section: Introductionmentioning
confidence: 96%